Body image dissatisfaction and social anxiety among Jaffna medical students - Nilani, S.; Krishika, P.; Bandara, S.M.S.H.; Madushika, D.M.D.U.; Kulenthiran, I.; Kumar, R.; Sivayokan, S. (University of Jaffna, 2024)
Background and objective: Body image dissatisfaction (BID) and social anxiety are known to be widely prevalent among young people. Within this group, medical students are no exception. The association between BID and social anxiety has been investigated in other settings, but not in Sri Lanka. This study aimed to determine the prevalence of BID and social anxiety, their associated factors and the relationship between BID and social anxiety among medical students at the University of Jaffna. Methods: An institution-based descriptive cross-sectional study was conducted among first to fourth year students of the Jaffna Medical Faculty from February 2022 to July 2023. Stratified random sampling by batch and gender was carried out to select the sample. Stunkard Figure Rating Scale and Social Phobia Inventory were used to measure BID and social anxiety, respectively. Chi square test was used to determine the associations (critical level 0.05). Results: A total of 349 students participated with response rate of 93%. Over two-thirds (67.9%, n=237) had BID, of whom 70% had positive dissatisfaction (greater body size than their perceived ideal) and 30% had negative dissatisfaction (lesser body size than their perceived ideal). There was a significant association between BID and body mass index (p<0.001), relationship status (p=0.049), and social media exposure (p=0.016); overweight students, those without partners and those exposed to social media for <2 hours were most likely to have BID. In the sample, 44.1% (n=154) of students had scores compatible with social anxiety. A significant association was found between social anxiety and sex (p=0.001) and social media exposure (p=0.016); female students and those who spend <2 hours on social media were more likely to have social anxiety. There was a significant association between BID and social anxiety (p=0.016); students with BID were more likely to have social anxiety. Conclusion and recommendations: The results suggest that a significant percentage of students of the Jaffna Medical Faculty have BID and social anxiety. More over, those with BID are more likely to have social anxiety. While research is needed to explore this relationship further, we recommend raising awareness and intervening to support students affected by with these mental health problems.
Keywords: Body image dissatisfaction; Social anxiety; Stunkard Figure Rating Scale; Social Phobia Inventory; Medical students